STRATEGI NAJIB RAZAK DALAM UPAYA PEMENANGAN PEMILIHAN RAYA MALAYSIA 2013 - Permadi, Arya Luthfi; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is aimed to see how Najib Razak uses his foreign policy attacking Sabah as his winning strategy on Malaysia Election â€œPemilihan Rayaâ€ in 2013. Najib Razak and his party, UMNO (United Malay National Organization) is not in good condition where it has lost many votes in 2008 election. Toward this situation, Najib Razak also faced Suluâ€™s Attack that is commited by MNLF.This research uses pluralism perspective and idiosincratic theory where stuffs related to personal life of the actor will influence the policy taken. The research methods is descriptive with library reasearch technique which used collect and elaborate the data and information from text book, journals, thesis and internet website.The result of this research shows that Najib Razak strategy has shown the result. â€œ1Malaysiaâ€ strategy that had benn used on fixing Najibâ€™s image has increase the people supports and votes. Najib Razak has also gotten the advantages from Sulu that contraining MNLF and Sabah conflict. Najib Razak use â€œSerangan Fajarâ€ attack in order to defend sovereigntyand figthing terrorism. Nationalism that occured from Malaysians made them voted Najib Razak on Malaysia 2013 Election by getting 133 chairs from 222 chairs that was competed.Keyword : Najib Razak, Sabah Conflict, 1Malaysia, MNLF